Manajemen Media Dakwah pada Era Globalisasi serta Tantangannya - Efendi, Erwan; Ilmi Nasution, Habib; As-singkily, Herdi (IAI Nasional Laa Roiba Bogor, 2024)
Da'wah media is a tool used as an intermediary in achieving the goals of da'wah. In conveying messages to recipients by utilizing media to achieve success, the choice of media used is very important. Progress in communication media in recent years has shown significant changes. Because there are many media that are used to convey messages to support da'wah activities, it is one of the effective and efficient ways of conveying Islamic values ​​to the public. Communication media can be interpreted as meaning that all media and objects can be used as communication media for the success of da'wah. Therefore, it is impossible for da'wah to be successful without the media to help make it a success. The more you master the use of media in the implementation of da'wah, the more it will lead to success and success in the implementation of da'wah.